Model-Based investigation of the effects of reactors' hydraulic retention times on phosphorus removal efficiency in an AO process - Yasar, Sumeyye; Manav Demir, Neslihan; Atci, Elif Burcu; Demir, Selami (PAMUKKALE UNIV, 2023)
This study presents the results of a simulation work performed using an activated sludge model to investigate the effects of reactors' hydraulic retention times (HRT) on phosphorus removal in a hypothetical anaerobic-oxic (AO) process. The simulations were performed for low, medium, and high influent phosphorus loads corresponding to influent C/P ratios of 100/1.0, 100/1.5, 100/2.0. For each of influent phosphorus loads, various anaerobic volume fractions (AVF) between 0.125 and 0.625 were used to test the response of the process that was investigated as a result of the change in hydraulic retention times. Additionally, removal efficiencies for chemical oxygen demand (COD), total nitrogen (TN), total phosphorus (TP), and total suspended solids (TSS) were also calculated. As a result of the study, maximum COD removal efficiencies for 100/2.0, 100/1.5 and 100/1.0 influent C/P ratios were determined as 91.8% for 0.250 AVF (for 100/2.0 and 100/1.5), and 91.7% for both 0.125 and 0.250 AVF, respectively. In all influent C/P ratios, the maximum TN removal efficiency was determined as 56.3% at 0.625 AVF, and the maximum TSS removal efficiency was determined as 93.3% at 0.125 AVF. Maximum TP removal efficiencies were determined as 92.8%, 90.8% and 86.2% for 100/2, 100/1.5 and 100/1 input C/P ratios at 0.375 AVF, respectively. Results showed that total phosphorus (TP) removal efficiency is determined by both influent C/P ratio and AVF in AO process. Of these, the effect of AVF is more prominent. For efficient removal of phosphorus, AVF ratios of 0.25 to 0.375 should be employed.
Keywords: Activated sludge model; AO process; Reactor volumes; Phosphorus removal; WASTE-WATER; Engineering